Principles of prophylactic and therapeutic management of skin toxicity during treatment with checkpoint inhibitors - Kamińska-Winciorek, Grażyna; Cybulska-Stopa, Bożena; Ługowska, Iwona; Ziobro, Marek; Rutkowski, Piotr (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2019)
The introduction of immunotherapy into the treatment of cancer patients has revolutionised the oncological approach and significantly improved patient survival. The key drugs are immune checkpoint inhibitors (CPIs), whose mechanism of action is to elicit immune response against cancer cell antigens. Three types of CPIs are currently used and approved: an anti-CTLA-4 antibody, ipilimumab; anti-PD-1 antibodies, nivolumab and pembrolizumab; and anti-PD-L1 antibodies: atezolizumab, avelumab and durvalumab. CPIs have been widely used in metastatic and adjuvant melanoma settings, metastatic lung cancer, Hodgkin’s lymphoma, renal cancer, bladder cancer, head and neck tumours, and Merkel cell carcinoma. However, side effects of CPIs differ from toxicities of other oncological drugs. According to literature data, in 10–30% of patients CPIs are responsible for immune-related adverse events (irAE) associated with excessive activation of the immune system. Systemic irAEs include enterocolitis, pneumonitis, hepatitis, nephritis, hypophysitis, and autoimmune thyroid disease. However, the most common irAEs of checkpoint inhibitors are dermatologic toxicities ranging from pruritus and mild dermatoses to severe reactions including Stevens-Johnson syndrome and toxic epidermal necrolysis. Each irAE can become serious if not early diagnosed and appropriately treated. In the article we present different types of skin irAEs related to CPIs together with the recommended therapies.